Effectiveness of Realistic Mathematics Approach to Increasing Mathematical Representation Ability at SMP N 9 Purwokerto - Hidayat, Liza Dian; Mawaddah, Silvina; Novikasari, Ifada (International Journal of Research in Mathematics Education, 2023)
This research was conducted based on the low ability of students' mathematical representation in class VIII SMP N 9 Purwokerto. One of the contributing factors is that the use of the learning approach used has not facilitated students in developing mathematical representation abilities. The solution that is considered capable of increasing the ability of mathematical representation is to apply learning with a realistic mathematical approach. The realistic mathematics approach provides opportunities for students to do modeling, depicting and symbolizing related to concrete problems. This research is a quantitative research with a quasi-experimental type with Nonequivalent Control Group Design. The population in this study were all students of class VIII SMP N 9 Purwokerto. The sample in this study was class VIII A with a total of 36 students and VIII B with a total of 36 students. The data analysis used is the z-test and the N-Gain test. The results of this study indicate that the realistic mathematical approach is effective in increasing students' mathematical representation abilities. From the results of the z-test showed a significant effect, the mathematical representation abilities of the experimental class students were higher. Then the results of the N-Gain test showed that the experimental class was in the medium category and the control class was in the low category. Thus the representation ability of the experimental class students is higher than that of the control class.